THE IMPACT OF ECOLOGICAL INNOVATIONS ON THE COMPETITIVE ADVANTAGES OF HOTEL BUSINESS ENTERPRISES - Нікітіна, Тетяна; Князь, Каріна (SWorldJournal, 2025)
The paper examines the issues of using environmental innovations and their impact on increasing the competitiveness of hotel enterprises. It is relevant to determine the effect of using environmental innovations as a tool for increasing the competitivenes